Beginners to professionals: how openness helps companies along their innovation journey - Visnjic, Ivanka (Henry Stewart Talks, 2022)
Quality over quantity, Innovation maturity levels, Case Study: FC Barcelona, Barca Innovation Hub, Innovation at Enel